A model for the quasistatic growth of cracks with fractional dimension. (May 2017) - Dal Maso, Gianni; Morandotti, Marco
Abstract: We study a variational model for the quasistatic growth of cracks with fractional dimension in brittle materials. We give a minimal set of properties of the collection of admissible cracks which ensure the existence of a quasistatic evolution. Both the antiplane and the planar cases are treated.